Revised Ordinances of the City of Fort Worth, Texas, 1873-1884, at 206, An Ordinance in Regard to Carrying Deadly Weapons, § 1 (1885) - (:unkn) unknown (General Publisher, 1873)
That it shall be unlawful for any person to carry about his person any pistol, Bowie knife or other deadly or unlawful weapon while within the corporate limits of this city
--
Keywords: CARRY